ELGO electric motorcycle: Design and analysis of trail-type electric motorcycle frame using finite element analysis - Muhammad Fatiy Elmoudi; Delima Yanti Sari; Yufrizal (Researcher and Lecturer Society, 2024)
The frame is an important part of the motorcycle as it carries the load of the passenger. Therefore, it is necessary to design a frame that can withstand the load and is lightweight. A lighter motorcycle will reduce the power required to ride it. This research aims to redesign the frame of a trail-type ELGO electric motorbike by considering a reduction in frame weight. The research was carried out using finite element analysis. The data from the analysis were checked based on the maximum stress not exceeding the yield strength of the DIN 1.0030 material and the safety factor greater than 1. The results showed that the newly designed frame has a lighter weight, with a maximum stress less than the yield strength of the DIN 1.0030 material and a safety factor value greater than 1. The simulation results also indicate the potential for further research by showing the maximum and minimum stress areas on the frame.